Highly accelerated, Dixon-based non-contrast MR angiography versus high-pitch CT angiography - Zeilinger, Martin; Giese, Daniel; Schmidt, Michaela; May, Matthias; Janka, Rolf Matthias; Heiß, Rafael; Ammon, Fabian; Achenbach, Stephan; Uder, Michael; Treutlein, Christoph (Radiologia Medica, 2023)
Objectives: To compare a novel, non-contrast, flow-independent, 3D isotropic magnetic resonance angiography (MRA) sequence that combines respiration compensation, electrocardiogram (ECG)-triggering, undersampling, and Dixon water-fat separation with an ECG-triggered aortic high-pitch computed tomography angiography (CTA) of the aorta. Materials and methods: Twenty-five patients with recent CTA were scheduled for non-contrast MRA on a 3 T MRI. Aortic diameters and cross-sectional areas were measured on MRA and CTA using semiautomatic measurement tools at 11 aortic levels. Image quality was assessed independently by two radiologists on predefined aortic levels, including myocardium, proximal aortic branches, pulmonary veins and arteries, and the inferior (IVC) and superior vena cava (SVC). Image quality was assessed on a 5-point Likert scale. Results: All datasets showed diagnostic image quality. Visual grading was similar for MRA and CTA regarding overall image quality (0.71), systemic arterial image quality (p = 0.07–0.91) and pulmonary artery image quality (p = 0.05). Both readers favored MRA for SVC and IVC, while CTA was preferred for pulmonary veins (all p < 0.05). No significant difference was observed in aortic diameters or cross-sectional areas between native MRA and contrast-enhanced CTA (p = 0.08–0.94). Conclusion: The proposed non-contrast MRA enables robust imaging of the aorta, its proximal branches and the pulmonary arteries and great veins with image quality and aortic diameters and cross-sectional areas comparable to that of CTA. Moreover, this technique represents a suitable free-breathing alternative, without the use of contrast agents or ionizing radiation. Therefore, it is especially suitable for patients requiring repetitive imaging.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Angiography; Computed tomography; Follow-up studies; Magnetic resonance imaging